Investigation of the Presence in Human Urine of Mercapturic Acids Derived from Phenanthrene, a Representative Polycyclic Aromatic Hydrocarbon - Cheng, Guang (Chem Biol Interact, 2017)
Polycyclic aromatic hydrocarbons (PAH) are environmental carcinogens implicated as causes of cancer in certain industrial settings and in cigarette smokers. PAH require metabolic activation to exert their carcinogenic effects. One widely accepted pathway of metabolic activation proceeds through formation of “bay region” diol epoxides which are highly reactive with DNA and can cause mutations. Phenanthrene (Phe) is the simplest PAH with a bay region and an excellent model for the study of PAH metabolism. In previous studies in which [D(10)]Phe was administered to smokers, we observed higher levels of [D(10)]Phe-tetraols derived from [D(10)]Phe-diol epoxides in subjects who were null for the glutathione-S-transferase M1 (GSTM1) gene. We hypothesized that Phe-epoxides, the primary metabolites of Phe, were detoxified by glutathione conjugate formation, which would result ultimately in the excretion of the corresponding mercapturic acids in urine. We synthesized the four stereoisomeric mercapturic acids that would result from attack of glutathione on Phe-epoxides followed by normal processing of the conjugates. We also synthesized the corresponding dehydrated metabolites and sulfoxides. These 12 standards were used in liquid chromatography-nanoelectrospray ionization-high resolution tandem mass spectrometry analysis of urine samples from smokers and creosote workers, the latter exposed to unusually high levels of PAH. Only the sulfoxide derivatives were consistently detected in the urine of creosote workers; none of the compounds was detected in the urine of smokers. These results demonstrate a new pathway of PAH-mercapturic acid formation, but do not provide an explanation for the role of GSTM1 null status on Phe-tetraol formation.